One new species of the genus Microconema Liu, 2005 (Orthoptera: Tettigoniidae: Meconematinae) from Yunnan, China - Duan, Yanhao; Liu, Qing; Chang, Yanlin (Zootaxa, 2022)
This paper reports one new species of the genus Microconema Liu, 2015, i.e. Microconema arctilamina sp. nov., and provides the characteristics and habitus photographs. Illustrations of important morphology of Microconema clavata (Uvarov, 1933) are also provided for the first time. The materials examined (including type specimens) are deposited in the Museum of Hebei University.